2010
DOI: 10.1089/jmf.2009.0226
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclophosphamide-Induced Oxidative Stress in Brain by Dietary Inclusion of Red Dye Extracts from Sorghum (Sorghum bicolor) Stem

Abstract: The stem of sorghum is used as color additives in cooking meals and taken as beverages when steeped or boiled in water as folklore for the management of anemia and some other diseases. This study sought to assess the antioxidant and neuroprotective potentials of red dye extract from sorghum stem on cyclophosphamide-induced oxidative stress in rat brain. Wistar strain albino rats were fed diet supplemented with the red dye (0.5% and 1.0% inclusion) for 14 days. There was no significant difference (P > .05) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…The observed average feed intake and average weight gain/loss of the rats in each group during the 23 d experiment (Tables 2 and 3) suggest that the inclusion of sorghum straw dye in rat diets, neither affected appetite nor causes loss of body weight. This finding is consistent with an earlier study, where dietary inclusion of red sorghum straw dye caused no significant difference in the daily feed intake and weight gain of rats (Oboh et al, 2010). However, the weight loss observed 3 d after cisplatin administration (Table 3) is consistent with an earlier study which suggests cisplatin administration may lead to significant loss of body weight (Ö zdemir et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observed average feed intake and average weight gain/loss of the rats in each group during the 23 d experiment (Tables 2 and 3) suggest that the inclusion of sorghum straw dye in rat diets, neither affected appetite nor causes loss of body weight. This finding is consistent with an earlier study, where dietary inclusion of red sorghum straw dye caused no significant difference in the daily feed intake and weight gain of rats (Oboh et al, 2010). However, the weight loss observed 3 d after cisplatin administration (Table 3) is consistent with an earlier study which suggests cisplatin administration may lead to significant loss of body weight (Ö zdemir et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Groups I and II were fed basal diet (50% skimmed milk, 36% corn starch, 10% groundnut oil, and 4% mineral and vitamin premix) (Oboh et al, 2010), while Groups III and IV were fed basal diet supplemented with 0.5% and 1% sorghum straw dye, respectively, for 20 d before cisplatin administration. On day 20, Group I received sterile water (1 mL/kg, i.p.…”
Section: Experimental Design and Induction Of Nephrotoxicitymentioning
confidence: 99%
“…Other beneficial effects of sorghum and its derived products include their ability to improve glycemic response, prevent cancer and confer anti-inflammatory effects. Other studies in the literature have also reported that sorghum phenolic extracts exert a protective effect to help prevent the onset of neurodegenerative related diseases, confer antidiabetic and anticancer effects, reduce swelling (oedema) and lower the incidence of oesophageal cancer [83][84][85][86][87][88][89]. Evidence for this has been demonstrated in previous studies and recently summarized in the reviews of Girard & Awika [70] and Aruna & Visarada [65].…”
Section: Bioactive Constituents Of Sorghummentioning
confidence: 85%
“…To date, several in-vitro and animal model studies have highlighted the potential of sorghum grain components, such as polyphenols, to scavenge free radicals. (176,(181)(182)(183)(184) Unfortunately, these studies are limited in their ability to attribute direct antioxidant effects of sorghum, as they do not account for metabolic transformations and interactions that influence bioavailability and biological activity of the polyphenols in the body after ingestion. For example, it is unclear what transformations polyphenols undergo in vivo, from the oral cavity, through the gastrointestinal tract and after absorption and metabolism.…”
Section: Effects On Oxidative Stress Biomarkers and Plasma Antioxidanmentioning
confidence: 99%